UTILIZING GOOGLE CLASSROOM FOR ENGLISH INSTRUCTION: POSITIVE AND NEGATIVE IMPACTS IN A HIGH SCHOOL SETTING - Verlinsti Vania Tamala; Luh Putu Artini; Ni Luh Putu Eka Sulistia Dewi (Esteem Journal of English Education Study Programme, 2024)
The integration of digital platforms in education has become increasingly prevalent, particularly in response to the need for remote learning solutions. This study aims to explore the structure of teaching and learning activities using Google Classroom in learning English and to find out the impacts of using Google Classroom in Learning English. The subjects of this study were 30 students of science class XI at Senior High School 3 of West Seram, Maluku, Indonesia. This study employed qualitative research. The data was collected through documentation and in-depth interview. The result of this study revealed that teaching and learning activities using Google Classroom run for approximately one semester. The students and teacher utilized Google Classroom to discuss the materials and submit the assignment through the platform’s features. This study also presented the positive and negative impacts of using Google Classroom in Learning English. The positive impacts are increased student participation, ease of assignment submission, the flexibility to learn from anywhere at any time, saving time and energy to learn, and even improvements in reading, writing, and listening skills in English. Conversely, the negative impacts are the students feeling frustrated and restless, tendencies towards procrastination, and instances of plagiarism.